Participação da neurotransmissão orexinérgica nas respostas respiratórias à hipercarbia e hipóxia em iguanas verdes e girinos de rã-touro - Fonseca, Elisa Maioqui (Universidade Federal de São Carlos, 2019)
Orexins (ORXs) are peptides produced by a group of neurons of the hypothalamus which regulate various physiological functions - such as the sleep-wake cycle, eating behavior, blood pressure, and respiration. These neurons are responsive to changes in pCO2/pH and hypoxia; and its effects on breathing involve participation in chemoreflexes. The vast majority of studies on ORXs and their contribution to respiratory modulation have been performed in mammals, especially rodents. The only work conducted in a non-mammalian vertebrate is one work from our group that demonstrated that ORX receptor-1 (OX1R) contributes to hypercarbia and hypoxia chemoreflexes in adult toads. This thesis, therefore, was designed to evaluate the role of ORXs in respiratory control in bullfrog tadpoles by recording respiratory activity in in vitro brainstem preparations; and in green iguanas through “in vivo” ventilation recordings. We observed that ORXs participate in ventilatory responses to hypercarbia in these two classes of vertebrates; but only in tadpoles they participate in ventilatory responses to hypoxia as well. In the case of the tadpoles, our experiments have shown that ORXs act in an inhibitory manner on O2 and CO2 chemoreflexes, while in iguanas, they act on CO2 chemoreflexes in an excitatory way.
Contribution of orexin neurotransmission to the respiratory responses to hypercarbia and hypoxia in green iguanas and bullfrog tadpoles
Keywords: Controle respiratório; Hipóxia; Hipercapnia; Orexina; Iguana verde; Girino de rã-touro; Respiratory control; Hypoxia; Hypercapnia; Green iguana; Bullfrog tadpole; CIENCIAS BIOLOGICAS::FISIOLOGIA